2004
DOI: 10.2165/00003088-200443100-00001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics and Pharmacodynamics of Tacrolimus in Solid Organ Transplantation

Abstract: The aim of this review is to analyse critically the recent literature on the clinical pharmacokinetics and pharmacodynamics of tacrolimus in solid organ transplant recipients. Dosage and target concentration recommendations for tacrolimus vary from centre to centre, and large pharmacokinetic variability makes it difficult to predict what concentration will be achieved with a particular dose or dosage change. Therapeutic ranges have not been based on statistical approaches. The majority of pharmacokinetic studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
799
7
12

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 784 publications
(838 citation statements)
references
References 254 publications
20
799
7
12
Order By: Relevance
“…However, while we observed that a single injection with FK506 improved fear conditioned memory function in Tg2576 mice, prolonged treatment of humans with FK506 has been reported to be associated with significant side effects, most notably nephrotoxicity (Olyaei et al, 2001;Baran et al, 2004;Staatz and Tett, 2004). Therefore, before considering clinically attractive the idea of CaN inhibitors for treating AD, future studies will have to determine whether lower, less nephrotoxic doses of FK506 administered for longer periods of time still provide behavioral benefits or whether novel behaviorally-active drugs that selectively target only CaN in the CNS could eventually be designed.…”
Section: Discussionmentioning
confidence: 76%
“…However, while we observed that a single injection with FK506 improved fear conditioned memory function in Tg2576 mice, prolonged treatment of humans with FK506 has been reported to be associated with significant side effects, most notably nephrotoxicity (Olyaei et al, 2001;Baran et al, 2004;Staatz and Tett, 2004). Therefore, before considering clinically attractive the idea of CaN inhibitors for treating AD, future studies will have to determine whether lower, less nephrotoxic doses of FK506 administered for longer periods of time still provide behavioral benefits or whether novel behaviorally-active drugs that selectively target only CaN in the CNS could eventually be designed.…”
Section: Discussionmentioning
confidence: 76%
“…The reason for the lower exposure for MR tacrolimus on d 84 is still unclear. It is well known that many factors infl uence the PK profiles of tacrolimus [1] . In this study, the patients were all in stable condition, and any drug known to alter the CYP450 enzyme system was prohibited before and during the study period to avoid drug-drug interaction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been marketed mainly for preventing or treating graft rejection in solid organ transplantation [1,2] . Tacrolimus has a narrow therapeutic window, and its bioavailability shows high interand intra-individual variability [1,3,4] . The systemic exposure AUC is a significant efficacy variable; therefore, therapy is optimized on an individual patient basis by monitoring trough levels as surrogate markers of exposure.…”
Section: Introductionmentioning
confidence: 99%
“…TAC is the drug of choice for living donor liver transplant recipients in our university hospital, Kyoto Prefectural University of Medicine. The pharmacokinetics (PK) of TAC are characterized by a marked and unexplained variability, particularly in the early period after transplantation [5,6]. TAC is highly lipophilic and insoluble in water, and is a substrate for the drug efflux pump, P-glycoprotein (Pgp), and the metabolizing enzyme, cytochrome P450 (CYP) 3A.…”
Section: Introductionmentioning
confidence: 99%